Jelly Fermented Soy Whey as Antioxidants Source of Alternative Functional Food - Lailiya A, Rizqi Nabilatul; Wahyuningsih, Dita; Hidayah, Wihda Wihdatul; Aminin, Agustina L. N. (JURNAL SAINS DAN MATEMATIKA, 2014)
Soy tofu whey is residual water in the process of tofu manufacturing which is derived from the remaining soy milk clotting. Tofu whey contains bioactive compounds which have been studied previously could be potential as an antioxidant, antimicrobial, anti-mutagenic, and antihypertensive. This study aim was to produce pleasant JF-Soywhey and make society healthy. Manufacturing of JF-Soywhey was conducted through a whey tofu fermentation process using Kefir grains at room temperature (Â± 28Â°C) for 48 hours and subsequently processed into jelly. The results showed that the products varied with fruit juice got a favoured by the panellists. In addition, the antioxidant content of products was still quite high as the ripening effects lowered the antioxidant capacity of 13.9%. Hence it could be suggested that the kefir grain fermented tofu whey could be used as an antioxidant source alternative functional food such as JF-Soywhey.